Rancang Bangun Sistem Kontrol Robot Line Follower Menggunakan Logika Fuzzy - Anggoro Mukti; Oky Dwi Nurhayati; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Line follower robot is a robot that can follow a line composed of a series of electronic components are equipped with wheels and driven by a motor. Controlling speed is very dependent on the speed limit and friction between the tire robot with the floor. The robots are designed to navigate and move automatically follow a flow line in order to get a response and speed are ideal.. The system consists of hardware and software. The hardware consists of a sensor such as a photodiode input, ATMEGA32 as microcontroller and DC motors. fuzzy logic is divided into three processes namely fuzzyfikasi, evaluation and defuzzyfikasi rule. Defuzzification a conversion step in fuzzy logic system to keluaran crisp value. The conversion result is an action taken by Fuzzy logic control system. The test results were obtained system is capable of identifying a straight line, turn lanes, and lane gray. The system is able to provide an ideal response and speed. input from the reading of the line will be processed by the control system fuzzy and outputs the result as the calculating of the motor speed. fuzzy control system can be an alternative technology development line follower robot control system.